Targeted Neuromodulation of Abnormal Interhemispheric Connectivity to Promote Neural Plasticity and Recovery of Arm Function after Stroke: A Randomized Crossover Clinical Trial Study Protocol. (12th March 2018) - Borich, Michael R.; Wolf, Steven L.; Tan, Andrew Q.; Palmer, Jacqueline A.
Abstract : Background . Despite intensive rehabilitation efforts, most stroke survivors have persistent functional disability of the paretic arm and hand. These motor impairments may be due in part to maladaptive changes in structural and functional connections between brain regions. The following early stage clinical trial study protocol describes a noninvasive brain stimulation approach to target transcallosally mediated interhemispheric connections between the ipsi- and contralesional motor cortices (iM1 and cM1) using corticocortical paired associative stimulation (ihPAS). This clinical trial aims to characterize ihPAS-induced modulation of interhemispheric connectivity and the effect on motor skill performance and learning in chronic stroke survivors. Methods/Design . A repeated-measures, cross-over design study will recruit 20 individuals post-stroke with chronic mild–moderate paretic arm impairment. Each participant will complete an active ihPAS and control ihPAS session. Assessments of cortical excitability and motor skill performance will be conducted prior to and at four time points following the ihPAS intervention. The primary outcome measures will be: TMS-evoked interhemispheric motor connectivity, corticomotor excitability, and response time on a modified serial reaction time task. Discussion/Conclusion . The findings from this single-site early stage clinical trial will provide foundational results to inform the design of larger-scale, multisite clinical trials to evaluate the therapeutic potential of ihPAS-based neuromodulation for upper limb recovery after stroke. This trial is registered with NCT02465034 .